(untitled) (Innovative professional education, 2024)
Awareness of the key role of the teacher in the process of vocational training at colleges determines the need for continuous purposeful development of the professional competence of the college teacher. The starting points for the concept of the development of professional competence of teaching staff at vocational colleges were the humanization of the educational process and the theoretical and methodological foundations of continuous professional education. The concept was focused on the development of structural components of a teacher’s professional competence, as an integrative property of the individual (Motivation and Value, Cognitive-information, Behaviour and Activity, Personal Reflection, Emotion and Volition); as well as on the development of the main types of teacher’s professional activity at a vocational college (educational, methodical, subject, informational and digital, environmental, inclusive, research and communicative competences).